Antimicrobial resistance and virulence profiles of Enterococcus spp. isolated from horses in korea. (October 2016) - Kim, Dae Ho; Chung, Yeon Soo; Park, Young Kyung; Yang, Soo-Jin; Lim, Suk kyung; Park, Yong Ho; Park, Kun Taek
Highlights: Horse-associated Enterococcus isolates were obtained in Korea. Of 260 isolates, 23.8% was defined as antimicrobial-resistant (AR) enterococci. Seven isolates (2.7%) were defined as multidrug-resistant enterococci. Clonal transmission of AR enterococci was detected in five horse facilities. This highlights the risk of AR Enterococcus transmission from horses to humans. Abstract: Antimicrobial-resistant (AR) enterococci have emerged as leading nosocomial pathogens. Transmission of AR Enterococci from animals to humans has been demonstrated. However, there is limited information on the transmission of enterococci from horses to humans. To address this issue, we characterized 260 enterococci isolated from horse-associated samples in Korea in 2013 based on their AR profiles and virulence traits. AR profiling revealed an average ratio of AR enterococci of 23.8%. Seven isolates (2.7%) were multidrug-resistant Enterococcus faecalis . Most tetracycline-resistant enterococci harbored either tetM or tetL or both genes; genes conferring resistance to other antimicrobials were detected at low rates. Biofilm formation and gelatinase activity were observed in 51.1% and 47.7% of isolates, respectively; most were E. faecalis harboring the gelE gene. Evidence of transmission of AR enterococci between horses and their environments was provided by pulsed-field gel electrophoresis, and highlights the risk of AR enterococcus transmission to horse riders and handlers through close contact.